Clinical significance of Helicobacter pylori infection in iron-deficiency anemia: features of comprehensive treatment approach - I. V. Mayev; S. A. Kochetov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2016)
Aim of investigation. To study pathogenic and clinical role of Helicobacter pylori infection at irondeficiency anemia (IDA). To present the diagnostic and treatment guidelines for these patients taking into account their specific requirements. Material and methods. Overall 120 H. pylori-positive patients of different age (from 18 to 70 years), which were subdivided into two groups were studied. The main group included 70 H. pylori-positive patients with chronic iron-deficiency anemia of unknown etiology. Patients of this group have been randomized in two homogeneous subgroups (according to severity of anemia). Patients of the subgroup 1a underwent eradication therapy for 10 days (amoxicillin 1000 mg b.i.d., clarithromycin 500 mg b.i.d.; esomeprazole 20 mg b.i.d.) followed by the course of treatment by ferrous iron combined to ascorbic acid. Subgroup 1b patients received only iron supplementation therapy. The group of comparison included 50 H. pylori-positive patients without coexistent iron deficiency who received the first line eradication therapy for 10 days as well. Presence of H. pylori infection and eradication control were carried out by urea breath test (Helic-test system). Efficacy of IDA treatment was evaluated by hemoglobin level, RBC color index, total iron-binding capacity (TIBC), serum ferritin and iron levels. Results. Patients were monitored with examination on the 14th, 28th and 56th days of treatment. Mean laboratory scores prior to onset of treatment in the subgroup 1a were: Нb 88,5 g/l, RBC 3,0×1012, RBC color index 0,74, serum iron 6,7 µmol/l, TIBC 89,4 µmol/l, transferrin saturation rate 9,3 %, ferritin 10,1 µg/l; in the subgroup 1B: 89,6 g/l, 3,1×1012, 0,75; 7,3 µmol/l, 88,6 µmol/l, 9,8%, 10,8 µg/l. At control examination in 28 days after iron supplementation onset positive changes were observed, that were more prominent in the subgroup 1a: Hb 117,8 g/l, RBC 3,9×1012, RBC color index 0,83, serum iron 17,7 µmol/l, TIBC 74,4 µmol/l, transferrin saturation percent 20,8 %, ferritin of 20,7 µg/l; in the subgroup 1B: 104,2 g/l, 3,6×1012, 0,81, 12,6 µmol/l, 79,2 µmol/l, 16,6 %, 17,9 µg/l respectively. Is also noticed that regression of anemia symptoms was more rapid than improvement of the laboratory scores especially in subgroup 1A patients. To 56th day of treatment all patients have reached target hemoglobin levels, that corresponded to a normal range. Conclusions. Eradication therapy in patients with iron deficiency anemia, allows to achieve improvement of both physical signs and the laboratory scores in shorter terms, as well as more rapid symptom relief. According to Maastricht IV consensus statements, all H. pylori-positive patients with idiopathic iron deficiency anemia require eradication therapy before onset of iron supplementation.